Neuronal ICAM-5 Inhibits Microglia Adhesion and Phagocytosis and Promotes an Anti-inflammatory Response in LPS Stimulated Microglia - Paetau, Sonja; Rolova, Taisia; Ning, Lin; Gahmberg, Carl G. (Frontiers in Molecular Neuroscience, 2017)
The intercellular adhesion molecule-5 (ICAM-5) regulates neurite outgrowth and synaptic maturation. ICAM-5 overexpression in the hippocampal neurons induces filopodia formation in vitro. Since microglia are known to prune supernumerous synapses during development, we characterized the regulatory effect of ICAM-5 on microglia. ICAM-5 was released as a soluble protein from N-methyl-D-aspartic acid (NMDA)-treated neurons and bound by microglia. ICAM-5 promoted down-regulation of adhesion and phagocytosis in vitro. Microglia formed large cell clusters on ICAM-5-coated surfaces whereas they adhered and spread on the related molecule ICAM-1. ICAM-5 further reduced the secretion of the proinflammatory cytokines tumor necrosis factor α (TNF-α) and interleukin 1β (IL-1β), but on the contrary induced the secretion of the anti-inflammatory IL-10 from lipopolysaccharide (LPS) stimulated microglia. Thus, ICAM-5 might be involved in the regulation of microglia in both health and disease, playing an important neuroprotective role when the brain is under immune challenges and as a “don’t-eat-me” signal when it is solubilized from active synapses.